Effectiveness of TENS (Transcutaneous Electrical Nerve Stimulation) In Knee Osteoarthritis Patient In Reducing Pain - Hanidah, Daniya Rizqiyani; Zakiyah, Hanna; Alpiah, Dini Nur (Worldwide Research Publishing, 2024)
Osteoarthritis (OA) of the knee is a common medical condition among the elderly population, often causing chronic pain, stiffness, and reduced quality of life. Pharmacological therapy to treat pain in knee OA has limitations, and this is why non-pharmacological therapy such as TENS (Transcutaneous Electrical Nerve Stimulation) Therapy has become an interesting research subject. Evaluate the effectiveness of TENS in reducing pain in patients with knee OA. The research methods involved a thorough literature review of clinical studies that have been conducted in recent years. Analysis of data from these studies aimed to identify trends and general findings regarding the use of TENS in managing pain in knee OA. From 4 journals used as literature reviews, it shows that TENS can significantly reduce the level of pain in patients with knee OA with a significance of P <0.001. Larger and more diverse studies tend to support the effectiveness of TENS, although there are variations in other findings. In addition to reducing pain, TENS also has the potential to improve joint function and the patient's quality of life